Digital currency - The driving force of development and its comprehensive impact on the socio-economic system - Phan , Minh Xuân (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
In the context of the global digital revolution, digital currencies, including cryptocurrencies such as Bitcoin, Ethereum, USDT and Central Bank Digital Currency (CBDC) projects, are gradually asserting their important role in reshaping the modern financial system. This trend has not only attracted the attention of developed countries such as the US, China and the EU but has also been promoted in developing countries such as Vietnam. According to statistics, the total capitalization of the global cryptocurrency market has surpassed the 2.87 trillion USD mark in 2024, while about 21.2% of Vietnam’s population has ever traded or invested in cryptocurrencies. This article will present an overview of the market, analyze the impact of digital currencies on the socio-economy and propose development trends as well as specific policy recommendations.